Assessing Difficulties Encountered by Dental Students Studying Oral Pathology and Addressing Their Concerns - Swati Saawarn (Journal of Clinical and Diagnostic Research, 2016)
Introduction: The present scenario of Oral Pathology and Oral Histology as a subject is alarming. In spite of so many advancements in terms of books, internet and conferences there are still lacunae between the understanding and interest for the subjects in the students. It can be partly due to the fact that the students perceive it as a non-clinical subject having a lesser scope for practice. Aim: The present study was aimed at evaluating the students approach towards oral pathology department and the subject. The purpose of the study was to analyze practical hurdles encountered by students and to find out solutions to overcome them. Materials and Methods: The cross-sectional questionnaire based study was done with BDS students of People’s Dental Academy, Bhopal, India, to gauge the understanding of their knowledge in the subject of Oral Pathology and Oral Histology. Questionnaire comprised of 28 multiple choice questions under five parameters. The data recorded was subjected to statistical analysis using chi-square test. Results: We found that study samples were efficient enough in terms of following instructions related to their day to day training. Although they were content with light microscope, they thought that some more interactive sessions could be beneficial for them in Oral Pathology. Conclusion: Through our study we found out that the students are well oriented on the whole about Oral Pathology. They certainly encounter difficulties which are easy to handle if proper measures are taken. We through our study would like the readers to be aware of the changing trends in teaching and to incorporate them routinely.